A review of the evidence to support electrical stimulation-induced vascularization in engineered tissue - Ying-tong Wang; Xiao-ting Meng (Regenerative Therapy, 2023)
Tissue engineering presents a promising solution for regenerative medicine and the success depends on the supply of oxygen/nutrients to the cells by rapid vascularization. More and more technologies are being developed to facilitate vascularization of engineered tissues. In this review, we indicated that a regulatory system which influences all angiogenesis associated cells to achieve their desired functional state is ideal for the construction of vascularized engineered tissues in vitro. We presented the evidence that electrical stimulation (ES) enhances the synergistic promotion of co-cultured angiogenesis associated cells and its potential regulatory mechanisms, highlighted the potential advantages of a combination of mesenchymal stem cells (MSCs), endothelial cells (ECs) and ES to achieve tissue vascularization, with particular emphasis on the different biological pathways of ES-regulated ECs. Finally, we proposed the future direction of using ES to reconstruct engineered tissue blood vessels, pointed out the potential advantages and disadvantages of ES application on tissue vascularization.